Ulos batak natural dye paste from salaon leaf extract (Indigofera tinctoria L), ketapang leaf (Terminalia catappa), and cocoa fruit peel (Theobroma cacao L) - Nadia Givani Sihotang; Ruth Yohana Saragih; Dewan Dinata Tarigan; Mika Yohana Pakpahan; Dafit Ericson Sihotang; Saronom Silaban; Murniaty Simorangkir (Jurnal Pendidikan Kimia (JPKIM), 2023)
Ulos is a type of traditional woven fabric that is often used for traditional ceremonies in the Batak tribe. Although ulos with natural dyes are more valuable, ulos weavers have switched to synthetic dyes due to the difficulty of the dyeing process with natural dyes. This research aims to make natural dyes from extracts of plants. Salaon plants (Indigofera tinctoria L), ketapang (Terminalia catappa), and cocoa (Theobroma cacao L) are types of plants that are easily available in the North Sumatra region and can be used as natural dyes. BATAK-Co (BATAK-Colour): ulos batak natural dye paste is a dyeing product in the form of a paste that can be used to dye yarn to be woven into ulos. The product is made through an extraction and fixation process with whiting, tunjung, and alum, as well as deposition and filtering processes, so that a BATAK-Co product is obtained: Ulos Batak Natural Coloring Paste with 3 color choices, namely blue from salaon leaf extract, black from ketapang leaf extract, and red from cocoa fruit peel extract. The spectra of the three dyestuffs have been identified using FT-IR. Through the entrepreneurship student creativity program, BATAK-Co: ulos batak natural dye paste products have been produced, packaged, and marketed both directly to ulos weavers and through social media, and have a great opportunity to become new entrepreneurs.Keywords: Cocoa; Ketapang; Natural dyes; Salaon; Ulos batak